Quality of medical services - recent challenges - Kowalczuk, Krystyna; Krajewska-Kułak, Elżbieta; Jankowiak, Barbara; Kowalewska, Beata; Rolka, Hanna (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Transitions in the health care system in Poland are orientated to support effective medical services and improve economy of the system. These changes set high requirements towards medical care staff. In free-market economy support high quality of medical services is an important condition of the functioning health care system and particular departments. In this article are presented implementations of high quality medical services on the basis of the research of publications in Poland and abroad. Nursing Topics 2010; 1 (1): 79-80